Mitochondria as a Target for Mitigating Sarcopenia - Coen, Paul M.; Musci, Robert V.; Hinkley, J. Matthew; Miller, Benjamin F. (Frontiers in Physiology, 2019)
Sarcopenia is the loss of muscle mass, strength, and physical function that is characteristic of aging. The progression of sarcopenia is gradual but may be accelerated by periods of muscle loss during physical inactivity secondary to illness or injury. The loss of mobility and independence and increased comorbidities associated with sarcopenia represent a major healthcare challenge for older adults. Mitochondrial dysfunction and impaired proteostatic mechanisms are important contributors to the complex etiology of sarcopenia. As such, interventions that target improving mitochondrial function and proteostatic maintenance could mitigate or treat sarcopenia. Exercise is currently the only effective option to treat sarcopenia and does so, in part, by improving mitochondrial energetics and protein turnover. Exercise interventions also serve as a discovery tool to identify molecular targets for development of alternative therapies to treat sarcopenia. In summary, we review the evidence linking mitochondria and proteostatic maintenance to sarcopenia and discuss the therapeutic potential of interventions addressing these two factors to mitigate sarcopenia.